2013
DOI: 10.1097/mej.0b013e328358bf5a
|View full text |Cite
|
Sign up to set email alerts
|

A telephone-based case-management intervention reduces healthcare utilization for frequent emergency department visitors

Abstract: Our results indicate that the nurse-managed telephone-based case-management intervention represents a possible strategy to improve care for frequent emergency department users as well as decrease outpatient visits, admission days and healthcare costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(144 citation statements)
references
References 17 publications
2
142
0
Order By: Relevance
“…This suggests that CM services may not appeal to some frequent users, who may benefit from alternative outreach strategies. However, this enrollment rate is comparable to those of other studies, 13 and we recruited an adequate number of participants based on power calculations. Although we anticipated a dropout rate of 30 %, we retained 78 % of study participants.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…This suggests that CM services may not appeal to some frequent users, who may benefit from alternative outreach strategies. However, this enrollment rate is comparable to those of other studies, 13 and we recruited an adequate number of participants based on power calculations. Although we anticipated a dropout rate of 30 %, we retained 78 % of study participants.…”
Section: Discussionsupporting
confidence: 58%
“…15,34 The non-significant reduction in ED use found in this study underscores the mixed evidence in the literature. At least seven prior studies 12,13,[35][36][37][38][39] showed ED use reductions following a CM or similar intervention, while five studies 9,11,14,40,41 did not. In terms of study design, sample size and intervention (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations